Blasting for Fracturing and Improving the Permeability of Deep, Soft, Outburst Prone Coal Seams Using Blasthole and Relief Hole Drilled into the Underlying Stratum: Optimal Hole Distance - Jianyu Zhang; Xingguo Zhao; Shigui Fu; Guodong Qiao; Xin Zhang; Shuai Yang (Geofluids)
To address the problems with deep-hole presplit blasting intended to fracture and improve the permeability of deeply buried, soft, high-gas-content coal seams, a method using a blasthole and a relief hole drilled into the underlying rock stratum was proposed. By establishing a theoretical model for this purpose, the stress wave propagation characteristics during the blasting process were analyzed, and the working mechanisms of the relief hole and the stress transmission characteristics were investigated. The blasting of the C13-1 coal seam in the Huainan mining area under different in situ stress conditions using different blasthole–relief hole distances was simulated using an implicit–explicit coupled method and the ANSYS/LS-DYNA software. The results showed that the blasting-induced stress wave was reflected from the coal–rock interface and transformed into a tensile wave owing to the different wave impedances of coal and rock, thereby fracturing the rock and coal masses better and achieving the intended permeability improvement effect. A free surface effect was produced near the relief hole during the blasting process, which directed the stress wave to propagate in the direction of the relief hole, thereby promoting fracturing in that direction. The in situ stress inhibited the blasting-induced fracturing in the coal mass. Thus, for blasting intended to improve the permeability of deeply buried coal masses, the blasthole–relief hole distance should be reduced to achieve better fracturing. Our results have a certain reference value for directional blasting intended to fracture and improve the permeability of deeply buried, soft, high-gas-content coal seams.